HUBUNGAN POWER FAKTOR ISOLASI TERHADAP KEMAMPUAN ISOLASI TRANSFORMATOR DAYA 150/20 KV - Mujiman -; Aru Purba Ardian Niagara (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2017)
Isolation transformer is a critical part of the power transformer, insulation deterioration or failure can cause failure of the operation or even damage the transformer. One method to determine the condition of the insulation is by testing with test equipment tangent delta 4000. In a study conducted, will be testing three-winding transformer isolation using test equipment delta 4000, function test equipment delta 4000 to measure the deterioration of the insulation used as insulating oil, paper and ceramics by measuring the power factor. After testing the insulation transformer three windings using test equipment delta 4000, the test result data was analyzed by comparing the value of the power factor of the standard manufacturer with test results using test equipment delta 4000, when comparing the results are the increase in the value of the power factor in data from tests conducted but the increase in the value of the power factor being tested is still on alert limits because some relationships insulation in the test value exceeds> 0.5 of the standard manufacturer is 0.2. However, these data need to be considered further because the value of the power factor should not be more than one.